DASENG SANGGALUHANG: A COMMUNITY WISDOM IN MANAGING MARITIME AND FISHERIES RESOURCE - Abdul Latif Bustami (LITERASI: Indonesian Journal of Humanities, 2011)
This article discusses daseng sanggaluhang as fishing community’s wisdom in managing maritime and fisheries resource in District Tatoareng Island, Sangihe Regency, North Sulawesi. For the discussion, it uses a qualitative design for analyzing field data collected through in-depth interviews, participant observation, and document studies. The article has some conclusions. Firstly, daseng Sanggaluhang by setting up a temporary home at the location of fishing ground for 3-6 months in accordance with customary rules loads on the suggestion and the prohibition in the management of marine resources and fisheries equipped with social sanctions for noncompliance. Secondly, daseng carries out in accordance with the dynamics of the community through strengthening the rule of customary rules through formal regulation. Thirdly, daseng functions as meaningful cosmos purification, conservation ecology, communalism, and regeneration principles. Fourthly, daseng loads rule-based ecological conservation that substantially contributes to the future of fishing communities themselves, especially to ensure ecological, social, and economic sustainability as a model of maritime development and sustainable fisheries. Keyword: community wisdom, daseng Sanggaluhang, Sangihe Island